Alluvial architecture of reworked pyroclastic deposits in peri-volcanic basins: Castillo Formation (Albian) of the Golfo San Jorge basin, Argentina - Paredes, José M. (2015)
Fil: Paredes, José M. Universidad Nacional de la Patagonia; Argentina